Theory and practice in student teaching - Lardizabal, Amparo S.; Campos, Milagros A. (Quezon City, Philippines : Katha Publishing Co, Inc., 1999)
Growing as a teacher needs observation and imitation of good models. It needs being able to discriminate between what is good teaching and what is not. It needs being able to analyze good points and weak points and being able to suggest remedies for the better. It needs a knowledge of child psychology and ability to establish rapport with children of different natures, abilities and interests. Recalling basic knowledge in Methods and Principles of Teaching, Child Psychology, Educational Psychology, Guidance and Counseling and other professional courses in Education, observing one's peers, supervising teachers and holding conferences with them are sure ways to grow.
I. Student Teaching: Definition, Rationale, Readiness and Importance -- II. The School and the Classroom Environment -- III. The Teacher -- IV. The Pupils -- V. Classroom Management and Discipline -- VI. Objectives -- VII. Lesson Planning -- VIII. Teaching Strategies and Instructional Materials -- IX. Motivation -- X. The Recitation and the Art of Questioning -- XI. The Assignment -- XII. Co-Curricular and Extra-Curricular Activities -- XIII. The Teacher and His Role in Guidance -- XIV. Conference and Evaluation.
Keywords: STUDENT TEACHING